Faktor-faktor yang Berhubungan dengan Status Menarche di SMP X di Rangkabitung - Sinaga, Sarma Eko Natalia (Coping: Community of Publishing in Nursing, 2015)
The purpose of this study is to determine the relationship among age, IMT,Sport activities, father”s occupation, father”s educatin level, father’s income, exposure of adult media and menarche status of the students of Junior High School (SMP) X in rangkasbitung. The study was conducted with qualitative approach and used cross-sectional research design onto total 106 (one hundred and six) respondents. The result of the bivariate analysis using Chi-square test shows a significant relationship among age (p = 0.00,? ? 0.05), IMT (p = 000, ? ? 0.05) and menarche status. Besides, the result of the logistic regression test shows that respondents exposure of adult media is two times more influencing toward their menarche status. Therefore, the school is suggested to estabilish a communication, information and education (KIE) or a periodical counseling program on the issue of reproductive health as well as factors that affect menarche.
Keywords: Menarche age, teenagers, reproduction health